2018
DOI: 10.1109/tbcas.2018.2828703
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analog Front End for Proton Range Detection in Hadron Therapy

Abstract: Clinical ions beams for cancer treatment provide maximum energy deposition (Bragg peak (BP)) at the end of their range and practically no dose behind. This enables a more efficient therapeutic option comparing with classical photon-based radiotherapy where maximum energy is deposited at the body interface. Obviously, minimum-error BP detection is, thus, a key aspect of this treatment. This paper investigates a promising detection technique, based on the so-called ionoacoustic effect. The BP energy deposition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…On top of that, acoustic sensors have a finite bandwidth in their frequency responses. Due to the underlying physics of signal generation, the frequency spectrum of proton‐induced acoustic waveforms mainly stays in the low‐frequency region (<50 kHz), 10,25 much lower than that of the transducers used in ultrasound imaging (~MHz). The physical size (cross‐section) of each sensor, if larger than the pixel size (3 mm), may also compromise the reconstruction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…On top of that, acoustic sensors have a finite bandwidth in their frequency responses. Due to the underlying physics of signal generation, the frequency spectrum of proton‐induced acoustic waveforms mainly stays in the low‐frequency region (<50 kHz), 10,25 much lower than that of the transducers used in ultrasound imaging (~MHz). The physical size (cross‐section) of each sensor, if larger than the pixel size (3 mm), may also compromise the reconstruction accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Each differential volume element of the irradiated source pressure emits a micro bipolar pressure wave. The pressure measured in the sensor is the sum of the micro-pressure waves emitted by each differential element of the volume [35]. Doubling the number of particles in a given pulse will double the resulting emitted pressure amplitude.…”
Section: Thermoacousticmentioning
confidence: 99%
“…They successfully evaluated the range error in anthropomorphic imaging phantom by coregistering IA and acoustic echo images 22,23 . Furthermore, to increase the SNR, a design of a low‐noise acoustic analog front‐end was presented by Riva et al 24 . and Vallicelli et al., 25 which was demonstrated to be useful in monitoring the high dose rate (FLASH) hadron therapy treatments 26 .…”
Section: Introductionmentioning
confidence: 99%
“…They successfully evaluated the range error in anthropomorphic imaging phantom by coregistering IA and acoustic echo images. 22,23 Furthermore, to increase the SNR, a design of a low-noise acoustic analog front-end was presented by Riva et al 24 and Vallicelli et al, 25 which was demonstrated to be useful in monitoring the high dose rate (FLASH) hadron therapy treatments. 26 Moreover, to increase the magnitude of pressure, we explored a fixed-field alternating gradient accelerator (FFA), a candidate accelerator in future proton therapy, 27,28 to generate a short-pulsed proton beam (σ∼27 ns).…”
Section: Introductionmentioning
confidence: 99%